2022
DOI: 10.1177/21925682221103588
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Subsidence Following Anterior Lumbar Interbody Fusion

Abstract: Study Design Retrospective cohort Objective Anterior lumbar interbody fusion (ALIF) may be complicated by subsidence, which can lead to significant morbidity including pain, disc space collapse, neural compression, segmental kyphosis, instability, and vertebral body fracture. This study sought to identify patient and procedural risk factors for subsidence in patients undergoing ALIF. Methods This study analyzed consecutive patients who underwent ALIF at a single institution with a minimum of 2 years follow-up.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…20 Notably, several other demographic and surgery-related factors have been associated with the functional and clinical outcomes described in the studies included in this review. A study from Zavras et al 49 50 who found a positive association between obesity and increased rates of subsidence amongst patients who underwent ALIF. Regarding patient surgical characteristics, Peng et al 51 in a review of 32 patients undergoing ALIF, found that lower intraoperative pressure and complete removal of the intraoperative plate was associated with significantly reduced cage retropulsion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20 Notably, several other demographic and surgery-related factors have been associated with the functional and clinical outcomes described in the studies included in this review. A study from Zavras et al 49 50 who found a positive association between obesity and increased rates of subsidence amongst patients who underwent ALIF. Regarding patient surgical characteristics, Peng et al 51 in a review of 32 patients undergoing ALIF, found that lower intraoperative pressure and complete removal of the intraoperative plate was associated with significantly reduced cage retropulsion.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, several other demographic and surgery-related factors have been associated with the functional and clinical outcomes described in the studies included in this review. A study from Zavras et al [ 49 ] reviewing 144 patients who underwent anterior LIF (ALIF) found that older age, higher body mass index, patient frailty as quantified by the American Society of Anesthesiologists physical status classification grade, and a prior diagnosis of osteoporosis were each factors associated with increased subsidence. Similar results were described by Phan et al [ 50 ] who found a positive association between obesity and increased rates of subsidence amongst patients who underwent ALIF.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between cage position and cage subsidence remains controversial. Zavras et al 32 showed that anterior cage placement is an independent risk factor for cage subsidence in ALIF. However, posterior cage placement is also a suggested risk factor for cage subsidence.…”
Section: Significance Of Osseous Endplate On Cage Subsidencementioning
confidence: 99%
“…But long-term follow-up after surgery shows that the intervertebral height may be lost. This can lead to instrumentation failure, pseudoarthrosis, kyphotic deformity, adjacent-segment disease, and loss of foraminal height, any of which can lead to recurrent nerve root impingement and radicular pain (2)(3)(4). And studies have shown that cage subsidence is associated with postoperative revision surgery, and the rate of revision is significantly higher in patients with high-grade cage subsidence after fusion, there are some studies showed the rate of cage subsidence can reach 38% (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…And studies have shown that cage subsidence is associated with postoperative revision surgery, and the rate of revision is significantly higher in patients with high-grade cage subsidence after fusion, there are some studies showed the rate of cage subsidence can reach 38% (5-7). Previous clinical studies have shown risk factors of cage subsidence (2)(3)(4)(5)8). But currently, it is rare to comprehensively use multiple relevant risk factors to predict and analyze the risk of subsidence.…”
Section: Introductionmentioning
confidence: 99%